Fatigue failure analysis of fillet welded joints used in offshore structures - Djavit, Djan Eirik; Erik, Strande (My University, 2013)
Classification societies advise against the use of fillet welds in joints used in marine structures where fatigue failure has major consequences. The main reason for this is due to less reliable non-destructive examination results compared to full penetration joints. However, fillet welds are used in most offshore designs due to geometry and fabrication of the structure. In such cases, fatigue cracks can be initiated and grow not only from the weld toe to the base material but also from the weld root through the fillet weld or into the section under welding The purpose of this thesis is to provide the designer with an improved knowledge of different fatigue calculation methods used in the maritime industry today, with the aim of decreasing the probability of failure with a higher control of a fatigue failure site. To provide an overview of the different fatigue calculation methods, a comparison study was performed, as well as a local weld parameter study for two fillet welded joints. The two methods used for this study were the structural hot spot and effective notch stress method. The two fillet welded joints were provided by Aker Solutions MMO AS, Bergen, Norway for this study. The first joint is a rectangular hollow section from a davit, built as a truss. The second model is a part of a K-joint from the platform Songa Trym. Both joints were analysed using a fine 3-D finite element model. The two different fatigue life calculations methods yielded a different fatigue life for the weld toe, with inconclusive results regarding their conservatism. An increased weld toe radius gave a higher fatigue life for the weld toe, while the larger weld size increased the fatigue life in the weld root. Any weld size effect regarding fatigue life in the weld toe could not be established. Based on the effective notch stress method calculations, there was an indication of weld root failure for the Songa Trym K-joint. Fatigue life improvement methods only increasing weld toe fatigue life are not recommended based on these results.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering